Efficient Detection of Longitudinal Bacteria Fission Using Transfer Learning in Deep Neural Networks - Garcia-Perez, Carlos; Ito, Keiichi; Geijo, Javier; Feldbauer, Roman; Schreiber, Nico; zu Castell, Wolfgang (Frontiers in Microbiology, 2021)
A very common way to classify bacteria is through microscopic images. Microscopic cell counting is a widely used technique to measure microbial growth. To date, fully automated methodologies are available for accurate and fast measurements, yet for bacteria dividing longitudinally, as in the case of Candidatus Thiosymbion oneisti, its cell count mainly remains manual. The identification of this type of cell division is important because helps to detect undergoing cellular division from those which are not dividing once the sample is fixed. Our solution automates the classification of longitudinal division by using a machine learning method called Residual Network. By means of transfer learning, we train a model in less time compared to one trained from scratch. This potentially eliminates most of the manual labor of classifying the type of bacteria cell division. The approach is useful in automatically labeling certain bacteria division after detecting and segmenting (extracting) individual bacteria images from microscopic images of colonies.